2022
DOI: 10.1177/87569728221133093
|View full text |Cite
|
Sign up to set email alerts
|

How Inclusive Leadership Influences Voice Behavior in Construction Project Teams: A Social Identity Perspective

Abstract: Voice behavior of project team members (PTMs), defined as the process in which PTMs proactively share ideas, concerns, and opinions about work-related issues to improve the status quo of projects, is pivotal but underexplored in construction projects. Using social identity theory, this study investigated how inclusive leadership influences PTMs’ voice behavior with survey data from 232 construction PTMs. The results indicated that inclusive leadership predicts PTMs’ promotive and prohibitive voice behavior, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…The findings of this study indicated that the total effects of inclusive leadership on teachers’ promotive voice and prohibitive voice behavior are significant, thus demonstrating that inclusive leadership style, as a form of positive organizational support, influences teachers’ extrarole behavior 19 , 86 , 87 . These results are consistent with the findings of previous research 21 , 22 , 24 .…”
Section: Discussionmentioning
confidence: 68%
“…The findings of this study indicated that the total effects of inclusive leadership on teachers’ promotive voice and prohibitive voice behavior are significant, thus demonstrating that inclusive leadership style, as a form of positive organizational support, influences teachers’ extrarole behavior 19 , 86 , 87 . These results are consistent with the findings of previous research 21 , 22 , 24 .…”
Section: Discussionmentioning
confidence: 68%
“…becomes closely wedded to the value of the new occupation." Since then, social identity theory has been used in the investigation of client satisfaction and loyalty (Webber, 2011); construction workplace safety behavior (Andersen et al, 2015;Choi et al, 2017); project turnover intentions (Ding et al, 2017); career satisfaction (McKevitt et al, 2017); team member behavior (Petter and Carter, 2017); project labelling (Sergeeva, 2017); organizational citizenship behaviors for the environment (Wang et al, 2017); depletion in PM ego (Fang and Zhang, 2021); servant leadership and project success (Nauman et al, 2022); voice behavior (Jiang et al, 2023); and relational contracts (Wang and Chen, 2023).…”
Section: Social Identity Theorymentioning
confidence: 99%
“…, 2017); depletion in PM ego (Fang and Zhang, 2021); servant leadership and project success (Nauman et al. , 2022); voice behavior (Jiang et al. , 2023); and relational contracts (Wang and Chen, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%